Pengembangan Sistem Informasi Penjualan dan Persediaan Berbasis Web dengan Notifikasi Stok Real-Time Menggunakan Metode Design Thinking - Muhammad Fajrusshodiq F; Ghufron Zaida Muflih (Jurnal Kridatama Sains dan Teknologi, 2026)
This study aims to develop a web-based sales and inventory information system for Fotocopy Fajarsidik in Banjar City. The primary issue identified is that sales transactions and inventory records are still managed manually, resulting in potential recording errors, stock data inconsistencies, and delays in report generation. The method applied is Design Thinking, which consists of the stages of empathize, define, ideate, prototype, and test, using a user-centered approach. The results from black-box testing using the Boundary Value Analysis (BVA) approach indicate that the system achieved a 100% success rate across all testing scenarios. The system is capable of automating sales transaction recording, inventory management, and generating integrated, accurate reports. The novelty of this study lies in the integration of the Design Thinking approach in developing a user-oriented system, as well as the implementation of a real-time low-stock notification feature that is automatically displayed after user login. This feature not only provides minimum stock information but also serves as an early warning system to support proactive inventory control, distinguishing it from conventional approaches that lack automatic notification mechanisms. Therefore, the developed system can improve operational efficiency and support decision-making at Fotocopy Fajarsidik in Banjar City